2022
DOI: 10.1038/s41562-022-01294-x
|View full text |Cite
|
Sign up to set email alerts
|

The role of alpha oscillations in temporal binding within and across the senses

Abstract: An intriguing notion in cognitive neuroscience posits that alpha oscillations mould how the brain parses the constant influx of sensory signals into discrete perceptual events. Yet, the evidence is controversial and the underlying neural mechanism unclear. Further, it is unknown whether alpha oscillations influence observers’ perceptual sensitivity (i.e. temporal resolution) or their top-down biases to bind signals within and across the senses. Combining EEG, psychophysics and signal detection theory, this mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 77 publications
4
36
0
Order By: Relevance
“…Whilst low pre‐stimulus alpha power over occipito‐parietal electrodes predicted increased temporal audiovisual sensitivity, no effect of instantaneous alpha frequency was found. These results, along with those of another recent study (Buergers & Noppeney, 2022), cast doubt on the notion that peak alpha frequency is a determining factor in the temporal sensitivity of perception.…”
Section: Does Cognition Operate Rhythmically?mentioning
confidence: 63%
“…Whilst low pre‐stimulus alpha power over occipito‐parietal electrodes predicted increased temporal audiovisual sensitivity, no effect of instantaneous alpha frequency was found. These results, along with those of another recent study (Buergers & Noppeney, 2022), cast doubt on the notion that peak alpha frequency is a determining factor in the temporal sensitivity of perception.…”
Section: Does Cognition Operate Rhythmically?mentioning
confidence: 63%
“…One reason this relationship was not apparent in this study and ours could be that the TOJ task is a much harder and cognitively demanding task than the sound-induced flash illusion or the two-flash fusion task, and performance is therefore subject to multiple additional influences. Null results, however, have also been reported by Buergers and Noppeney (2022), who found strong evidence that individual peak-alpha frequency do not influence observers' perceptual sensitivity or bias for two-flash discrimination.…”
Section: Neither Individual Peak-alpha Frequency Nor Power Predicts I...mentioning
confidence: 63%
“…Given the set of null findings just cited, the relevance of the current work is twofold: firstly, it reinforces the idea that the phase of ongoing alpha band oscillations shapes our conscious perception, and that this contribution is critical in the integration and segregation of visual stimuli. Secondly, contrarily to Buergers and Noppeney (2022), we provide evidence of the role of ongoing alpha oscillations in pacing visual perception, by demonstrating a pattern of connectivity between V2 and MT critically specific to the upper alpha band and to the segregation of visual stimuli. Reasons of this discrepancy might have to be searched into the different sources of alpha oscillations (Womelsdorf et al, 2014), characterizing either topdown cortical influences (Van Kerkoerle et al, 2014; Halgren et al, 2019) or thalamo-cortical communications (Bollimunta et al, 2011; Hughes et al, 2011).…”
Section: Discussionmentioning
confidence: 78%
“…In fact, several recent works show no effect of alpha phase in stimuli detection (Ruzzoli et al, 2019), visual awareness and accuracy (Benwell et al, 2017, 2021) or reaction times (Vigué-Guix et al, 2020). In another study using both flashes and sounds, Buergers and Noppeney (2022) found no effect of alpha frequency (both as an individual trait and as a varying state) on visual integration, posing an important challenge to the claim that ongoing alpha oscillations impact the temporal precision of visual perception.…”
Section: Discussionmentioning
confidence: 96%